ADOLESCENCE TIBIAL TUBERCLE AVULSION FRACTURE: OPTION OF SURGICAL TREATMENT IN WORSENING CONDITION OF PRE-EXISTING OSGOOD-SCHLATTER DISEASE (OSD) - Fira Soraya; Ritzky Pratomo Affan; Bagus Danu Hariyanto (Journal Orthopaedi and Traumatology Surabaya)
Background: Osgood-Schlatter disease (OSD) is the most frequent cause of chronic knee pain in adolescents. Tibial tubercle avulsion fractures are an infrequent injury, approximately between 0.4-2.7% of all epiphyseal injury. Even though the relation between OSD and tibial tubercle avulsion fracture is still controversial, there are cases previously reported with this presentation.